Disruptive effects of natural disasters: The 1906 San Francisco Fire - Hanna M. Schwank (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Natural disasters are growing in frequency globally. Understanding how vulnerable populations respond to these disasters is essential for effective policy response. This paper explores the short- and long-run consequences of the 1906 San Francisco Fire, one of the largest urban fires in American history. Using linked Census records, I follow residents of San Francisco and their children from 1900 to 1940. Historical records suggest that exogenous factors such as wind and the availability of water determined where the fire stopped. I implement a spatial regression discontinuity design across the boundary of the razed area to identify the effect of the fire on those who lost their home to it. I find that in the short run, the fire displaced affected residents, forced them into lower paying occupations and out of entrepreneurship. Experiencing the disaster disrupted children's school attendance and led to an average loss of six months of education. While most effects attenuated over time, the negative effect on business ownership persists even in 1940, 34 years after the fire. Therefore, my findings reject the hope for a "reversal of fortune" for the victims, in contrast to what is found for more recent natural disasters such as hurricane Katrina.
Keywords: N91; N31; Q54; O15; J61; J62; 330; Natural Disasters; Internal Migration; Economic History; Regional and Urban Economics